A new energetics model for the assessment of the power-duration relationship during over-ground running - Vassallo, C.; Kilduff, L. P.; Cummins, C.; Murphy, A.; Gray, A.; Waldron, M. (European Journal of Sport Science, 2022)
We evaluated the reliability of an over-ground running three-minute all-out test (3MT) and compared this to traditional multiple-visit testing to determine the critical speed (CS) and distance > CS (D´). Using a novel energetics model during the 3MT, critical power (CP) and work > CP (W´) were also evaluated for reliability and compared to the multiple-visit tests. Over-ground running speed was measured using Global Positioning Systems during fixed-speed trials on a 400 m track to exhaustion, at four intensities corresponding to: (i) maximal oxygen uptake (VO2max) (Vmax), (ii) 110% VO2max(110%Vmax), (iii) Delta70% (i.e. 70% of the difference between gas exchange threshold and Vmax) and (iv) Delta85%. The participants subsequently performed the 3MT across two days to determine its reliability. There were no differences between the multiple-visit testing and the 3MT for CS (P = 0.328) and D´ (P = 0.919); however, CP (P = 0.02) and W´ (P < 0.001) were higher in the 3MT. The reliability of the 3MT was stable (P > 0.05) between trials for all variables, with coefficient of variation ranging from 2.0-8.1%. The current over-ground energetics model can reliably estimate CP and W´ based on GPS speed data during the 3MT, which supports its use for most athletic training and monitoring purposes. The reliability of the over-ground running 3MT for power- and speed-related indices was sufficient to detect typical training adaptations; however, it may overestimate CP (~ 25 W) and W´ (~ 7 kJ) compared to multiple-visit tests.